Combustion of Solid Fuel in a Vortex Furnace with Counter-swirling Flows - Redko A.A.; Redko I.A.; Redko A.F. (Problems of the Regional Energetics)
The results of computer simulation of the processes of incineration of low-grade solid fuel-pulverized peat with a moisture content of 40%, an ash content of 6% are given. It has been determined the fields of distribution of temperature, velocity of gases and particles in the volume and at the outlet from the furnace. The three-dimensional temperature distribution in the combustion chamber indicates high-temperature combustion of peat particles at temperatures above 1700°C with liquid ash removal in the lower part of the furnace. It has been determined that when the furnace is cooled, it is not ensured combustion of the fuel completely. The value of the swirling flow rate at the outlet from the furnace (up to 370 m/s) ensures the efficiency of separation of fuel particles, reducing heat losses from mechanical underburning. It is determined that the concentration of oxygen is close to zero over the entire height of the furnace, at an outlet from the furnace the oxygen concentration is 5...6%, since oxygen is supplied with excess (αв=1,2). The results of a numerical study showed that the diameter of peat particles affects the process of their combustion: coke particles with an initial diameter of 25 mkm to 250 mkm burn out by 96%. With an increase in particle diameter up to 1000 mkm, the degree of burn-out of coke decreases, but at the same time their removal decreases. It is shown that the furnace ensures the completeness of combustion of peat particles of peat 99.8%, volatiles is 100%.